Pelatihan Wisata Edukasi Interpretasi Flora pada Kelompok Sadar Wisata di Jalur Pendakian Propok Lombok Timur - I Gde Mertha; Agil Al Idrus; Abdul Muhyi Abidin; Lale Yaqutunnafis; Baiq Salkiah (Jurnal Pengabdian Magister Pendidikan IPA, 2021)
The hiking trail of Propok in the National Park of Rinjani mountain is very potential for educational tourism activities based on flora biodiversity. In the context of educational tourism, the Tourism Awareness Group (Pokdarwis) which plays a role in managing the Propok route needs to receive training on flora interpretation. This service aimed to provide an assistance in the practice of interpreting tree flora to tour guides from the Tourism Awareness Group on the Propok hiking trail. The method used was training and performance in the form of practical assistance combined with lecture, discussion, demonstration and question and answer. The training activities that had been carried out were practical assistance for tree flora interpretation activities and independent practice of flora interpretation, which was followed by trials on students in the field. The conclusion of this service reveal that (1) The flora interpretation training received a positive response from the training participants and got a very valuable experiences to improve their skills in educational tourism activities, (2) The great enthusiasm of the trainees in carrying out the practice of flora interpretation greatly supports the success of this training activity , and (3) The tree flora interpretation activity for students on the Propok hiking trail was well received, considered very useful and enjoyable. Thus, educational tourism activities can add to the tourist attraction on the Propok hiking trail